2023
DOI: 10.3390/foods12101935
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Different Packaging Conditions on Quality Stability of High-Pressure Treated Serra da Estrela Cheeses during Cold Storage

Abstract: Serra da Estrela cheese with a Protected Designation of Origin (PDO) is a traditional cheese that is wrapped in paper without vacuum. High-pressure processing (HPP), which requires vacuum packaging of the cheese, has been used for its cold pasteurization to overcome safety issues. In this study, two packaging systems were studied: non-vacuum greaseproof paper wrapping package and vacuum packaging in plastic film. Lactococci, lactobacilli, enterococci, and total mesophiles reached ca. 8 log cfu g−1 and 4–6 log … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The crude protein content (total nitrogen × 6.38) was determined using an automatic Kjeldahl analyzer (Kjeltectm 8400, Foss, Hilerod, Denmark). The nitrogen content in fractions of pH 4.6-souble nitrogen (pH 4.6-SN) was determined using the macro-Kjeldahl method [22][23][24]. Then, the nitrogen content in fractions of 12% trichloroacetic acid-SN (12% TCA-SN) and 5% phosphotungstic acid-SN (5% PTA-SN) was tested according to the macro-Kjeldahl method.…”
Section: Protein and Non-protein Nitrogenmentioning
confidence: 99%
“…The crude protein content (total nitrogen × 6.38) was determined using an automatic Kjeldahl analyzer (Kjeltectm 8400, Foss, Hilerod, Denmark). The nitrogen content in fractions of pH 4.6-souble nitrogen (pH 4.6-SN) was determined using the macro-Kjeldahl method [22][23][24]. Then, the nitrogen content in fractions of 12% trichloroacetic acid-SN (12% TCA-SN) and 5% phosphotungstic acid-SN (5% PTA-SN) was tested according to the macro-Kjeldahl method.…”
Section: Protein and Non-protein Nitrogenmentioning
confidence: 99%
“…High-pressure processing (HPP) is being increasingly applied and studied as a nonthermal alternative process to the conventional heat-based pasteurization processes used for dairy foods, including cheese, registering minimal deleterious effects on quality and a shelf-life extension up to 2-3-fold higher than the non-pasteurized counterparts [9]. However, the effects of HPP on cheese are dependent on the pressure intensity applied, the holding time used, and the ripening stage [10,11]. Only three studies were found that focused on the effect of HPP on lipolytic features during storage of raw cows' and ewes' milk cheeses [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the effects of HPP on cheese characteristics are dependent on the pressure level applied, the length of treatment, and particularly the stage of ripening at which HPP was applied. For example, to enable the safe storage of Serra da Estrela cheese under refrigeration over a prolonged period of 15 months without modification of its sensory attributes, HPP (450 MPa or 600 MPa for 6 min or 9 min) was applied and its impacts on the cheese properties were assessed [11]. HPP also deaccelerated proteolysis and had little effect on texture parameters and sensorial attributes [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation